National health surveys by mail or home interview: effects on response - Picavet, H (BMJ Group, 2001)
STUDY OBJECTIVE—To study the effect of using a mail questionnaire or home interviews on the size and the selectivity of response to national health surveys. DESIGN—The interview survey and the mail survey were both carried out in the same country (the Netherlands) using the same sample frame, the same study period (1998) and collected partly the same data on demographic, socioeconomic and health characteristics. SETTING—The Netherlands. PARTICIPANTS—Dutch non-institutionalised inhabitants aged 25 years and over. MAIN RESULTS—Response to the mail survey was lower (46.9%, n=3664) than to the interview survey (58.5%, n=6061). The mail survey gave higher response rates for women and lower response rates for persons with lower levels of education. Respondents to the mail survey reported lower rates of smoking but a slightly worse health status and higher figures on the use of health care services. No differences by method of data collection were found for age, marital status, region, household composition, work status and categories of body mass index. CONCLUSION—Although the response of the mail survey was lower than the home interview survey, respondents showed generally small differences, with exception of level of education.   Keywords: mail surveys; interview surveys; non-response